OPTIMIZATION OF TOFU WHEY CONCENTRATION IN COCONUT MILK NATA DE SKIM - Saleh, Nuriyya; Widjanarko, Simon Bambang (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
One of the uses of coconut milk scheme is for the production of Nata De Skim Santan using Acetobacter xylinum bacteria and the addition of tofu whey substrate. This study aims to determine the effect of whey concentration on the characteristics of nata de coconut milk and the right optimum whey concentration on making nata de coconut milk. The independent variable used X1= Whey concentration with a lower limit of 0% (-1) and an upper limit of 50% (+1). The responses observed were yield (Y1), nata thickness (Y2), and moisture content (Y3). The results showed that the use of whey concentration had an influence on the characteristics of nata de coconut milk with Fvalue for the yield model, thickness model, moisture content model, and whey was 17.94, 24.83, 14.72, and 14.72. The optimum concentration of whey that is right for making nata de coconut milk was 49.07% with a desirability value of 0.89, the optimum yield was 29.71%, the optimum thickness was 1.13 cm, and the optimum moisture content was 89.7%.